2020
DOI: 10.1101/2020.06.10.142893
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sentinelp16INK4a+ cells in the basement membrane form a reparative niche in the lung

Abstract: Senescent cells are recognized drivers of aging-related decline in organ function, but deciphering the biology of senescence in vivo has been hindered by the paucity of tools to track and isolate senescent cells in tissues1–4. Deleting senescent cells from transgenic murine models have demonstrated therapeutic benefits in numerous age-related diseases5–11, but the identity, behavior, and function of the senescent cells deleted in vivo remain elusive. We engineered an ultra-sensitive reporter of p16INK4a, a bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…(2) they lose their proliferative capacity in vivo; (3) their numbers are greater with age; (4) their half-lives varied among tissues; (5) this is the first report to perform a comprehensive transcriptomic analysis of p16 high cells in vivo at a single-cell level; (6) that based on the transcriptomics p16 high cells are highly heterogeneous depending on the tissue and cell type, though most of them are strongly related to age-related tissue dysfunction; and (7) the removal of p16 high cells ameliorated steatosis and inflammation in the liver of a NASH mouse model. Although the harmful effects of senolytic treatment on health have been reported (Grosse et al, 2020;de Mochel et al, 2020), our results suggest that an optimized senolytic treatment regimen might be beneficial for various age-associated disorders.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…(2) they lose their proliferative capacity in vivo; (3) their numbers are greater with age; (4) their half-lives varied among tissues; (5) this is the first report to perform a comprehensive transcriptomic analysis of p16 high cells in vivo at a single-cell level; (6) that based on the transcriptomics p16 high cells are highly heterogeneous depending on the tissue and cell type, though most of them are strongly related to age-related tissue dysfunction; and (7) the removal of p16 high cells ameliorated steatosis and inflammation in the liver of a NASH mouse model. Although the harmful effects of senolytic treatment on health have been reported (Grosse et al, 2020;de Mochel et al, 2020), our results suggest that an optimized senolytic treatment regimen might be beneficial for various age-associated disorders.…”
Section: Discussionmentioning
confidence: 60%
“…We detected Tom + p16 high cells in all tissues tested (Figures 2A and S2A). Recent studies reported contradictory results; one report showed that p16-positive cells were readily detected in lung shortly after birth (de Mochel et al, 2020) while in another report these cells were barely detectable in any of the tissues tested even at 2 months after birth (Grosse et al, 2020). In our model, we detected Tom + p16 high cells in all tissues of 2-month-old mice (see below), although the reason why the labeling sensitivities of the p16positive cells were varied among these studies is currently unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, depletion of senescent cells using senolytic drugs or genetic models has a beneficial effect against fibrosis and other age-related diseases in mice [29,30,51,60]. However, some ( pre-)senescent cells seem to be essential for homeostasis and repair in the mouse [61,62], highlighting the importance of understanding how cell-type-specific senescence modulates IPF.…”
Section: Regeneration Of a Diseased Lung Chronic Diseasesmentioning
confidence: 95%
“…In highly regenerative organisms, e.g., salamanders and zebrafish, senescent cells contribute to the regeneration of complex structures (11). A recent report suggests the presence of senescent fibroblasts in the developing and adult lung supporting epithelial progenitor cell function (12).…”
Section: Senescence In Repair and Developmentmentioning
confidence: 99%